Promoting Health Literacy in the Workplace Among Civil Servants: Cross-Sectional Study - Florence Carrouel; Benjamin du Sartz de Vigneulles; Céline Clément; Virginie-Eve Lvovschi; Elise Verot; Valeria Tantardini; Michel Lamure; Denis Bourgeois; Romain Lan; Claude Dussart (JMIR Publications, 2024)
Abstract BackgroundIn 2022, the World Health Organization highlighted the alarming state of oral health (OH) worldwide and urged action to include OH in initiatives on noncommunicable diseases. The population needs improved OH skills and attitudes and an adequate level of OH literacy (OHL) and general health literacy (HL). The implementation of health promotion actions in the workplace, which is a part of most people's lives, appears to be an opportunity. In France, civil servants have several socioprofessional levels and represent an excellent model with results transposable to the population. ObjectiveThis study aimed at determining the OHL and HL level of civil servants in France in order to implement specific prevention actions in their workplaces. MethodsA cross-sectional study of French civil servants was conducted in France from October 2023 to February 2024. Participants completed three validated questionnaires in French: (1) a questionnaire on OH knowledge, (2) the Oral Health Literacy Instrument, French version (OHLI-F; this is composed of reading comprehension and numeracy sections) to assess the OHL level, and (3) the Short Test of Functional Health Literacy in Adults, French version (s-TOFHLA-F) to assess the HL level. The scores for OH knowledge, the OHLI-F, and the s-TOFHLA-F were reported as means (SD) and the 95% CI. These scores were classified into 3 categories: adequate (75-100), marginal (60-74) and inadequate (0-59). ANOVA and binary logistic regression were performed. The OHLI-F reading comprehension and OHLI-F numeracy scores were compared using the Welch 2-sample tt ResultsA total of 1917 persons completed the 3 questionnaires, with adequate levels of OHL (n=1610, 84%), OH knowledge (n=1736, 90.6%), and HL (n=1915, 99.9%). The scores on the s-TOFHLA-F (mean 98.2, SD 2.8) were higher than the OHLI-F (mean 80.9, SD 7.9) and OH knowledge (mean 87.6, SD 10.5). The OHLI-F was highly correlated with OH knowledge (P<PPP ConclusionsSome French civil servants had inadequate or marginal levels of OH knowledge (n=181, 9.5%) and OHL (n=307, 16%) but none had an inadequate level of HL. Results highlighted the relevance of implementing OH promotion programs in the workplace. They should be nonstandardized, adapted to the literacy level of professional categories of workers, and focused on numeracy skills. Thus, appropriate preventive communication and improved literacy levels are the means to achieve greater disease equity and combat the burden of noncommunicable diseases.